PENGAWASAN DINAS LINGKUNGAN HIDUP DAN KEHUTANAN PROVINSI RIAU TERHADAP HUTAN DI KECAMATAN BATANG GANSAL KABUPATEN INDRAGIRI HULU TAHUN 2017 - Auliya Ichfuty Ichsan; M. Y. Tiyas Tinov (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Forest monitoring is carried out to track and assess the implementation of forest management, so that the objectives can be achieved optimally and at the same time provide feedback for further improvement or improvement of forest management, regional governments also supervise forests, communities and individuals also play a role in forest monitoring. The regional government is also authorized to carry out monitoring, request information and conduct checks on the implementation of forest supervision. As for the background of this research are 1.) Communities do encroachment of forest areas that are used for oil palm plantations without a permit.2.) Lack of forest security personnel Riau Province Environment and Forestry Service.This study aims to determine the supervision of the Riau Province Environment and Forestry Office on Forests in Batang Gansal Subdistrict, Indragiri Hulu Regency in 2017 and the obstacles faced by the Environment and Forestry Office in implementing forest surveillance in Batang Gansal District, Indragiri Hulu Regency in 2017. This study uses qualitative approach with descriptive research types. Data collection techniques used were interviews and documentation. Data analysis was done by descriptive method, namely by giving a general description of the research obtained from the interview by connecting it qualitatively.The results of the study showed that the supervision carried out by the Riau Province Environment and Forestry Service was not optimal, there were still some illegal practice activities found in the Forest area. There are obstacles in the implementation of supervision including the lack of forest security personnel and the ability and Human Resources (HR) to carry out the policies set, the location is too broad, the people who still do not understand the rules of forestry in terms of the importance of forests and forest benefits, and budget constraints.Keywords: Local Government, Supervision, Forest